DIGITAL INNOVATION: TRANSFORMING THE BUILDING MATERIALS TRADE BUSINESS TOWARD SUSTAINABILITY - จันทะเดช เทิดศักดิ์; เชียรวัฒนสุข กฤษดา (Thai Interdisciplinary and Sustainability Review, 2025)
This article presents approaches to developing service innovation that effectively integrates digital technologies within the building materials retail business, aiming to enhance competitiveness and promote long-term sustainability. Through a comprehensive review of relevant literature and empirical research, it synthesizes key concepts and practical evidence supporting applications in this sector. Digital innovation enables businesses to rapidly adapt to market changes, improve operational efficiency, reduce costs, and enrich customer experiences by providing timely, precise, and responsive services tailored to diverse needs. Core technologies include Artificial Intelligence (AI), the Internet of Things (IoT), Cloud Computing, and Big Data analytics, which can be seamlessly integrated into service delivery processes and organizational management systems. However, the digital transformation journey is often challenged by barriers such as employee resistance to change, high initial investment costs, data security concerns, digital skill gaps, and regulatory uncertainty, necessitating careful planning and systematic management strategies.